2020
DOI: 10.1088/1674-4926/41/3/032101
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial graphene gas sensors on SiC substrate with high sensitivity

Abstract: 2D material of graphene has inspired huge interest in fabricating of solid state gas sensors. In this work, epitaxial graphene, quasi-free-standing graphene, and CVD epitaxial graphene samples on SiC substrates are used to fabricate gas sensors. Defects are introduced into graphene using SF6 plasma treatment to improve the performance of the gas sensors. The epitaxial graphene shows high sensitivity to NO2 with response of 105.1% to 4 ppm NO2 and detection limit of 1 ppb. The higher sensitivity of epitaxial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…As a breakthrough outcome, recently, the electronic kilogram has been introduced. During the last decade, large efforts have been made to develop epitaxial graphene-based sensors for the detection of NO 2 [11][12][13], polar protic and polar aprotic vapors [14], solvents [15,16], Hall effect [17,18], illicit drugs (amphetamine or cocaine) [19], toxic heavy metals (cadmium, lead, and mercury) [20][21][22][23][24][25], ultraviolet (UV) light [26], and terahertz waves [27], etc. Notably, the above-listed examples of sensing applications concern only unmodified pristine epitaxial graphene.…”
Section: Introductionmentioning
confidence: 99%
“…As a breakthrough outcome, recently, the electronic kilogram has been introduced. During the last decade, large efforts have been made to develop epitaxial graphene-based sensors for the detection of NO 2 [11][12][13], polar protic and polar aprotic vapors [14], solvents [15,16], Hall effect [17,18], illicit drugs (amphetamine or cocaine) [19], toxic heavy metals (cadmium, lead, and mercury) [20][21][22][23][24][25], ultraviolet (UV) light [26], and terahertz waves [27], etc. Notably, the above-listed examples of sensing applications concern only unmodified pristine epitaxial graphene.…”
Section: Introductionmentioning
confidence: 99%
“…31 In this work, the relationship between current and voltage was measured to study the sensitivity, with ethanol concentration varying from 400 to 900 ppm. 32 In this paper, ethanol concentration was measured by an ethanol sensor. Figure 4a shows that the current increases with voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Much research has revealed the interactions among rivers, lakes and marshes, and proved the importance of river, lake and marsh protection and restoration from a system perspective. Yu et al (2020) monitored the water surface rate of river-lake-marsh systems in China from 1990 to 2010.…”
Section: Introductionmentioning
confidence: 99%